Draft Genome Sequence of the First NDM-1-Producing Providencia stuartii Strain Isolated in Portugal - Manageiro, Vera (Genome Announc, 2015)
We report here the draft genome sequence of the first NDM-1-producing Providencia stuartii strain isolated in Portugal. Sequence analyses revealed the presence of an incompatibility group A/C2 (IncA/C2) plasmid and of diverse acquired genes conferring resistance to β-lactams, aminoglycosides, tetracycline, macrolides, chloramphenicol, and sulfonamides. This sequence contributes to the evaluation of the spread of NDM-1 producers.